Diagnóstico ambiental em saúde: Ecoepidemiologia da Leishmaniose Tegumentar Americana no Estado do Acre - Ribeiro, Mateus Duarte (2013)
The aim of this study was to analyze the spatial distribution of American Cutaneous Leishmaniasis (ACL) in the State of Acre, between 2001 and 2010, through the analysis of the epidemiological profile and correlation analyses between the detection rate of the disease and housing conditions, sanitation and electricity. For this study we used the ACL cases reported in the State of Acre of the Brazilian System for Disease Notification (SINAN) and data from the Brazilian Institute of Geography and Statistics (IBGE). Two studies were conducted, the first describing the epidemiologic profile (Chapter 2) and the second correlating the ACL with housing conditions (Chapter 3). The analyses were conducted using multivariate analysis techniques and the software Statistica (Statsoft 7.0). According to SINAN, 10,984 cases of ACL were reported in the State of Acre in the study period. In the first study, the results showed there are clusterings of the epidemiological profile in the ACL patients in three groups. In the first group, the epidemiological profile consists of women, with predominance of ACL mucosa form, aged 20 years old, living and working in rural areas and forests; in the second group, the epidemiological profile consists of male patients, with ACL cutaneous form, older than 40 years old, living and working in urban areas; and the third group there was predominance of male patients, ACL cutaneous form, aged from 20 to 40 years old, living and working in rural areas. In the study on the housing conditions, the Principal Component Analysis (PCA) suggested a direct association between ACL and inadequate housing characteristics, such as collecting water rivers, lakes or streams and storing rain water, inadequate disposal of solid waste (dumped in vacant lots) and not having electricity in rural areas; and not having bathrooms or sanitation in urban and rural areas; the PCA also suggested an inverse association between the occurrence of ACL and sanitation using septic tanks in urban areas. It is possible that the hyper endemicity of ACL in that area is related to the adaptation of transmission cycles to peridomestic environments and spreading to previously nonendemic areas, as a result of unplanned urbanization and deforestation, and also the inadequate housing conditions contribute to increased population exposure to vectors of ACL.